The determinants of bank profitability in China - SHEN, DANYI (2019)
This study analyses the determinants of bank profitability in China during the period 2011 to 2018. System Generalized Method of Moments estimation will be used to evaluate the determinants of commercial banks’ profitability based on 53 Chinese commercial banks. There are specific financial indicators and macroeconomic determinants to examine bank profitability. Bank specific indicators include bank size, asset quality, capital adequacy, efficiency, liquidity, credit risk and insolvency risk. Macroeconomic variables are GDP growth and unemployment rate. The result indicates that efficiency, capital adequacy, credit risk and GDP growth have significant relationship with profitability of commercial banks in China. This paper gives suggestions and recommendations for Chinese commercial banks to increase profit of banking businesses.